2020
DOI: 10.1021/acs.nanolett.0c02440
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Oxide-Nitride Heterostructure as a Tunable Hyperbolic Metamaterial Platform

Abstract: Metal-free plasmonic metamaterials with wide-range tunable optical properties are highly desired for various components in future integrated optical devices. Designing a ceramic–ceramic hybrid metamaterial has been theoretically proposed as a solution to this critical optical material demand. However, the processing of such all-ceramic metamaterials is challenging due to difficulties in integrating two very dissimilar ceramic phases as one hybrid system. In this work, an oxide-nitride hybrid metamaterial combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
(75 reference statements)
0
38
0
Order By: Relevance
“…[ 43,44 ] Here, nanoscale NiO exhibits weak FM property as reported by prior studies. [ 45–47 ] Au exhibits good plasmonic properties and catalytic properties facilitating the nanowire growth. [ 48 ] Two growth processes were taken to explore the potentials in achieving ordered three‐phase structure as illustrated in Figure 1B: 1) a direct co‐deposition of three phases, 2) a template growth to direct the NiO nucleation on top of Au nanopillars.…”
Section: Figurementioning
confidence: 99%
“…[ 43,44 ] Here, nanoscale NiO exhibits weak FM property as reported by prior studies. [ 45–47 ] Au exhibits good plasmonic properties and catalytic properties facilitating the nanowire growth. [ 48 ] Two growth processes were taken to explore the potentials in achieving ordered three‐phase structure as illustrated in Figure 1B: 1) a direct co‐deposition of three phases, 2) a template growth to direct the NiO nucleation on top of Au nanopillars.…”
Section: Figurementioning
confidence: 99%
“…The permittivity of one typical metal–nitride Au–TiN [ 58 ] hybrid film is also shown in the plot, where the majority of ε || and ε ⊥ are all negative because of the metallic behaviors of both Au and TiN. More interestingly, a very recent study has demonstrated the NiO–TiN [ 59 ] hybrid VAN thin film, where the dielectric NiO phase presents the nanopillar morphology grown in the metallic TiN matrix, leading to ε || < 0, ε ⊥ > 0 with permittivity mainly located in the second quadrant (schematic illustration shown on the top left in the diagram). Table 1 summarizes the IP ( ε || ) and OP ( ε ⊥ ) permittivity values and functionalities for the reported VAN systems in the wavelength range of 400–1000 nm.…”
Section: Part I: Permittivity Of Oxides Nitrides Carbides and Van Thin Filmsmentioning
confidence: 99%
“…[47][48][49][50][51][52] The permittivity of common oxides, nitrides, carbides, and several explored VAN hybrid system in the wavelength range of 400-1000 nm are plotted in Figure 2. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] It can be seen that most of the pure oxides, carbides, and nitrides have isotropic positive permittivity values, i.e., nearly equal positive ε || and ε ⊥ values due to the (pseudo-) centrosymmetric structures. Thus the range of their permittivity values are located in the light-blue elliptical region in the first quadrant of the diagram, with a few exceptions of transition metal nitrides (i.e., TiN, HfN, and ZrN) with both negative ε || and ε ⊥ located in the third quadrant of the diagram.…”
Section: Part I: Permittivity Of Oxides Nitrides Carbides and Van Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations